Immunohistochemical Study of VEGF in Placenta of Hypertensive Mothers - H K, Sharath Kumar; N, Chaitra; G, Nataraju; M, Bharathi (Annals of Pathology and Laboratory Medicine, 2020)
Background: Pregnancy is most commonly complicated by Hypertensive disorders. In India, the incidence of gestational hypertension varies from 0.5-1.8%. VEGF is a prime regulator of angiogenesis and overall maintenance of endothelial cell health. This study aims to determine the role of VEGF in placentae of Hypertensive and Normotensive pregnancies by assessing its immunohistochemical expression in Syncytiotrophoblasts. Methods: The study was conducted in the Department of Pathology in our institute. This is a case-control study which included 50 placentae. Out of which,25 were from Normal mothers and 25 placentae from Hypertensive mothers. Immunohistochemistry for VEGF was performed on tissue section using commercially available monoclonal antibodies. The results were interpreted by evaluating Positivity and Intensity of Immunostaining. Result: Out of 25 Hypertensive placentae, 22 showed Positivity for VEGF immunostaining. Out of 25 Normotensive placentae, 23 showed Negative results for syncytiotrophoblastic staining of VEGF. The difference in VEGF expression in syncytiotrophoblast of hypertensive and normotensive placentae was statistically significant. Conclusion: Hypoxia acts as a potent stimulus for induction of VEGF mRNA in an attempt to normalize fetal blood flow and thus VEGF is increased. This results in the notable increase in immunohistochemical expression of VEGF in the syncytiotrophoblasts of hypertensive placenta.